The locus of care : families, communities, institutions, and the provision of welfare since antiquity - Horden, Peregrine; Smith, Richard (Richard Sydney William), 1952- (Studies in the social history of medicine., 1998)
The care of the needy and the sick is delivered by various groups including immediate family, the wider community, religious organisations and the State funded institutions. The Locus of Care provides an historical perspective on welfare detailing who carers were in the past, where care was provided, and how far the boundary between family and state or informal and organised institutions have changed over time. Eleven international contributors provide a wide-ranging examination of themes, such as child care, mental health, and provision for the elderly and question the idea that there has.